EFEKTIVITAS DAYA ANTI JAMUR DAUN SALAM (SYZYGIUM POLYANTHUM W) TERHADAP PERTUMBUHAN JAMUR CANDIDA ALBICANS DAN SUMBANGANNYA PADA PELAJARAN BIOLOGI DI SMA - Mery Angraini; Khoiron Nazip; Meilinda Meilinda (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2014)
Abstract: A studi about effect of Syzygium polyanthum W. leaves on Candida albicans was done. The objective of this experiment to know methanol S. polyanthum extract for impeding C. albicans growth as in vitro. The experiment used method of Completely Randomized Design (CRD) and analytical examination using F test by 6 treatments that are concentration of 1%, 2%, 3%, 4%, 5%, and 6% with 4 repetition. Pharameter was used namely transparant zone at aroung of papper disc. The result showed that methanolÂ S. polyanthum extract can impede C. albicans growth for concentration of 1%, 2% and 3% and the most active showed for concentration of 3%. Result also showed that methanol S. polyanthum extract can inhibi the growth of C. albicans with minimum inhibition concentration 1%. The conclusion that methanol S. polyanthum was potential as an antifungal toward C. albicans. Key words: Syzygium polyanthum W. leaves, antifungal, Candida albicans